SOSIALISASI PROGRAM KERJA KEGIATAN PENGABDIAN KEPADA MASYARAKAT DI DESA GOLADANO - Tatema Telaumbanua; Fatolosa Hulu; Baziduhu Laia (Haga : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this service activity is community service activities carried out by students of the teaching and education faculties of Nias Raya University, in the context of developing knowledge that is directly practiced in the community for the purpose of service. The method of implementing community service activities uses a conventional approach in the form of lectures where the community can directly conduct and prepare themselves to support community service activities. The results obtained are that the community is able to understand the community service activities and programs carried out in Goladano Village for 1 month of implementing the activity program and can improve the quality of the community regarding a new work program offered by the community, one of which is to encourage parents and children and students of the importance of education.